Theoretical analysis of radiative properties of pronucleus multicellular cyanobacteria. (February 2019) - Ma, C.Y.; Zhao, J.M.; Liu, L.H.
Highlights: Radiative properties of multicellular filamentous microalgae species were studied. Effect of cell wall and adjacent cells interaction on radiative properties were considered. Validated applicability of equivalent cylinder to predict radiative properties of filamentous microalgae. Polarization related Mueller scattering matrix elements were studied. Spirulina platensis with morphology of filamentous helix structure was studied. Abstract: Many species of cyanobacteria are of multicellular filamentous structure with chains of spherical or capsule monomer cells and having morphology of linear or spiral shape. In this paper, we built three models to represent such featured cyanobacteria cells and the effect of cell wall and adjacent monomer cell interaction on the radiative properties of the multicellular microalgae were studied using the discrete dipole approximation in the visible spectral region. The validity of equivalent volume and equivalent surface cylinder models on prediction of the radiative properties of the multicellular microalgae were examined. The extinction cross-section shows an overall decreased trend with wavelength in the spectral range 380 to 750 nm. The featured absorption peaks in the theoretically predicted spectral absorption cross-sections are consistent with experimental observations, which are corresponding to absorption of Chl a, phycocyanin and β -carotenoid. The scattering phase function exhibit strongly forward scattering peak due to the large size parameter of the cyanobacteria cells. The equivalent volume cylinder model generally gives better predictions on the extinction cross-section, absorption cross-section, and asymmetry factor of multicellular filamentous cyanobacteria.